Irrigation scenarios for artichokes and dry bean as a result of soil variability on the basis of resistivity mapping in southwest Italy - Alromeed, Alaa Aldin; Rossi, Roberta; Bitella, Gianfranco; Bochicchio, Rocco; Amato, Mariana (Italian Journal of Agronomy, 2015)
This work aims at comparing irrigation strategies on the basis of deficit irrigation and soil spatial variability assessed through electrical resistivity mapping (ERM) conducted by an automatic resistivity profiler on-the-go sensor. Profiles chosen along a range of soil electrical resistivity showed different soil properties linked to water holding capacity within a field, with total available water (TAW) values of the coarser-textured zone corresponding to about 50% of TAW in the finertextured zone within the field. Multi-year weather data were obtained on a daily basis and scenarios were developed for climatic demand conditions representing dry average and wet years. The ISAREG water balance and irrigation scheduling model was afterwards applied to the different soil profiles and with different strategies for full and deficit irrigation, to compute water and irrigation requirements as well as related yield impacts of deficit irrigation for artichokes and dry beans. Deficit irrigation allowed calculated water savings up to about 50% for the winter crop and 33% for the summer crop with yield losses lower than 10%. Irrigation requirements within irrigation strategy were 10 to 44% different between profiles, and this indicates that soil visualization techniques such as ERM can be used for the identification of zones for site-specific irrigation management.